2010
DOI: 10.1007/s12291-010-0069-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Serum Insulin Levels and Its Resistance With Biochemical, Clinical and Anthropometric Parameters in South Indian Children and Adolescents

Abstract: There is a rising trend in the prevalence of insulin resistance among obese, overweight children and adolescents. The serum insulin and its correlation with biochemical, clinical and anthropometric parameters were evaluated in 185 children and adolescents (59 control, 52 obese, 49 overweight, 25 congenital heart disease) of age group 10-17 years. The levels of serum insulin were measured by ELISA. Serum insulin levels were found to be significantly increased in children who were obese, overweight and had conge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
2
5
1
Order By: Relevance
“…Our results are in agreement with Sari et al, [30], who proposed that skin tags are frequently associated with the risk factors for metabolic syndrome (MS) and heart disease. Furthermore, Rao et al, [31] reported a positive correlation between serum insulin and BMI, plasma C-peptide, and plasma leptin, whereas, Shaheen et al, [32] demonstrated a positive correlation between leptin and HOMA-IR in obese patients suggesting that leptin displays an association with obesity and insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with Sari et al, [30], who proposed that skin tags are frequently associated with the risk factors for metabolic syndrome (MS) and heart disease. Furthermore, Rao et al, [31] reported a positive correlation between serum insulin and BMI, plasma C-peptide, and plasma leptin, whereas, Shaheen et al, [32] demonstrated a positive correlation between leptin and HOMA-IR in obese patients suggesting that leptin displays an association with obesity and insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…Atherosclerotic changes begin in the coronary arteries already during childhood. 21 In our study with pubertal obese children and adolescents, the groups did not present significant differences regarding changes in TC, HDL-c, TG, LDL-c, IR, insulin, glucose, ACN, and blood pressure levels. However, Lavrador et al, in their study of obese postpubertal adolescents between 14 and 19 years old, identified that the higher the degree of obesity, the greater the frequency of the changes evaluated, with significant differences for fasting plasma glucose, IR, TG, HDL-c, and blood pressure.…”
Section: Discussioncontrasting
confidence: 46%
“…Hyperinsulinism is the main risk factor for the occurrence of DM, HBP, and dyslipidemia. 21,22 Acanthosis nigricans, which is a clinical manifestation of hyperinsulinism, was found in 84% of the subjects studied, of whom 70% had elevated insulin and only 8.1% had abnormal levels of plasma glucose. Only 5.4% of the participants had elevated insulin with no ACN.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the finding of another study conducted in 2011. 17 Usually, patients' first consultation for acanthosis nigricans is with a dermatologist. High acanthosis nigricans neck grades (III and IV) and textures (II and III), as well as grade IV of axilla, correlate strongly with IR and can to help identify populations at risk in mass screening programmes.…”
Section: Discussionmentioning
confidence: 99%